Systematics of the Ocoee Salamander (Plethodontidae: Desmognathus ocoee), with description of two new species from the southern Blue Ridge Mountains - Pyron, R. Alexander; Beamer, David A. (Zootaxa, 2022)
The “mountain” dusky is a charismatic ecomorph of Dusky Salamander (Desmognathus): smaller ( 20–50mm SVL), more terrestrial and montane woodland species, typically with round tails and extremely variable, often colorful patterns. Originally considered a single species (D. ochrophaeus), populations across the Appalachians are now divided into D. abditus, D. carolinensis, D. ochrophaeus, D. ocoee, and D. orestes, which do not form a clade but are instead scattered across the phylogeny of Desmognathus. A Coastal Plain species with a mountain dusky phenotype (D. apalachicolae) is also nested within a lineage related to D. ocoee. Within the current concept of D. ocoee, there are up to 8 genetically distinct geographic lineages which display significantly different but substantially overlapping morphologies. Recent studies have suggested that as many as six species could reasonably be delimited based on genetic data. We evaluate the strength of that evidence here and find support for five species in the D. apalachicolae + D. ocoee group. The first is D. apalachicolae in essentially its originally described form from the Coastal Plain. The second and third are D. adatsihi sp. nov. and D. balsameus sp. nov., endemic to the Great Smoky/Plott Balsam and Great Balsam Mountains, respectively. The fourth corresponds to the resurrected D. perlapsus for populations from the Alarka and Cowee Mountains in North Carolina, through the Chattahoochee River drainage to the Fall Line in the Piedmont of Georgia and Alabama. The fifth is D. ocoee, here restricted to populations in the Nantahala and Unicoi Mountains and southernmost Blue Ridge escarpment, along with previously recognized populations from the Cumberland Escarpment and Cumberland Plateau of south-central Tennessee and northeastern Alabama. This taxon concept of D. ocoee includes three deeply divergent geographic genetic segments that hybridize across two contact zones, while D. apalachicolae may be nested within some southern Blue Ridge populations of D. ocoee. The resurrected form of D. perlapsus also exhibits some admixture with the newly restricted D. ocoee. While this taxonomic arrangement is robust and stably derived from mitochondrial, morphological, and nuclear data, more sophisticated future analyses sampling additional populations and loci to estimate relationships may reach more subtle conclusions regarding the identity of some lineages within D. ocoee.